Strategi Pemasaran Produk Impor di Pasar Lokal: Studi Kasus pada PT Mitra Mulia Pertiwi Nusantara - Nasar Buntu Laulita; Devinson Devinson (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This Community Service activity aims to analyze and develop marketing strategies for imported products at PT Mitra Mulia Pertiwi Nusantara in the local market of Batam. The methods used include direct observation, in-depth interviews with company representatives, and documentation studies to obtain a comprehensive picture of the implementation of the marketing mix (product, price, promotion, and distribution). The results of the analysis show that the company faces challenges in adjusting imported products to local consumer preferences, setting competitive prices, and optimizing promotion and distribution. Through this activity, marketing strategy recommendations have been developed, including improving market segmentation, utilizing digital media for promotion, adjusting prices based on competition, and optimizing distribution channels. The implementation of these recommendations is expected to increase the company's competitiveness and expand the market share of imported products amid increasingly fierce competition. This activity also provides academic contributions as a reference for the development of international marketing science and practical contributions for companies in formulating sustainable marketing strategies.